Recent Graduates’ and Language Teachers’ Assessments of ESP Preparation in Hungary - Feketéné Silye, Magdolna (Acta Agraria Debreceniensis, 2002)
Like many teachers of ESP in Hungarian higher education, I have for several years been spurred to track and investigate those interrelationships that exist between the expectations of the multicultural European job market of the 21st century and the linguistic literacy competencies required of those young graduates that are searching for jobs in such an environment. What specific knowledge or rather, what specific combination of knowledge, skills and cultural competencies do they need in order to succeed? Are we, language teachers aware of the responsibilities we have in preparing our students for such challenges? This paper publishes partial results of a national survey conducted in 2000. The investigations involved 120 teachers of ESP in higher education and 71 young graduates of technical universities or colleges with different profiles. The queries covered a wide range of issues of which we will only be examining one – from two perspectives, though – here: a.) The retrospective satisfaction of recent graduates with the language preparation they received and b.) The teachers’ assessment of the importance of the components of the preparation they provided.